Voltammetric determination of dopamine using modified glassy carbon electrode by electrografting of catechol - Pourghobadi Zeinab; Neamatollahi Davood (Journal of the Serbian Chemical Society, 2017)
By means of cyclic voltammetry as a diagnostic technique, the present study tried to describe the behaviour of dopamine (DP) at the bare and catechol electrografted glassy carbon electrode (CA/GCE). The results indicated that the CA/GCE exhibits high electrocatalytic activity toward DP. The DP cycling of the CA/GCE in DP showed two linear calibration ranges between 5.0–100 and 100–750 μM with a detection limit of 0.86 μM. For 6 DP replicate measurements (50 μM); the relative standard deviation (RSD) was 2.7 %. This method was successfully used for the determination of DP in serum samples.